Thin‐slice T2 MRI imaging predicts vascular pathology in hemifacial spasm: A case‐control study. Issue 10 (11th July 2014) - Sekula, Raymond F.; Frederickson, Andrew M.; Branstetter, Barton F.; Oskin, James E.; Stevens, Dale R.; Zwagerman, Nathan T.; Grandhi, Ramesh; Hughes, Marion A.
Abstract: Hemifacial spasm (HFS) is a condition that may severely reduce patients' quality of life. We sought to determine the sensitivity and specificity of thin‐slice T2 magnetic resonance imaging (MRI) for detecting vascular compression in HFS patients. Prospective information was collected on 28 patients with HFS who presented to our center between March 2011 and March 2012 with thin‐slice T2 MR imaging. The sensitivity and specificity for differentiating patients from controls were calculated. Sensitivities were 78.6% and 92.9% for the blinded radiologists and 75% for the partially blinded neurosurgeon. Specificities were 42.9% and 28.6% for the blinded radiologists and 75% for the partially blinded neurosurgeon. Magnetic resonance imaging of the facial nerve can guide clinicians in selecting patients who are good surgical candidates. Thin‐slice T2 MRI should be viewed as supportive rather than diagnostic. © 2014 International Parkinson and Movement Disorder Society